2020
DOI: 10.3390/atmos11080797
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Air Quality in a Highschool Gym Located in an Urban Area of Southern Poland—Preliminary Research

Abstract: The benefits of regular exercise include improved physical and mental health. The school gym is a particular micro-environment where students perform intensive physical training. The question is if there is an increased risk of microbiological contamination. This preliminary work studied the exposure of students to bacterial aerosol (BA) in a highschool gym located in an urban area of Southern Poland. A sampling of BA was undertaken with an Andersen six-stage impactor (ANDI). BA was identified using API (analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…In our study, seven other Bacillus species were identified in various samples, while in the aforementioned study by Brągoszewska and Pastuszka ( 2018 ), only four different species were found. Contrary to another study by Brągoszewska et al ( 2020 ), concerning indoor and outdoor microbiological air quality in a high school gym in Southern Poland, we did not isolate Corynebacterium . The reasons for such results are probably the differences in air sampling and the identification method.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, seven other Bacillus species were identified in various samples, while in the aforementioned study by Brągoszewska and Pastuszka ( 2018 ), only four different species were found. Contrary to another study by Brągoszewska et al ( 2020 ), concerning indoor and outdoor microbiological air quality in a high school gym in Southern Poland, we did not isolate Corynebacterium . The reasons for such results are probably the differences in air sampling and the identification method.…”
Section: Resultscontrasting
confidence: 99%
“…The reasons for such results are probably the differences in air sampling and the identification method. Brągoszewska et al ( 2020 ) used an Andersen six-stage impactor ANDI for sampling, but in case of identification, the MALDI-TOF method was used in our study, while biochemical API tests were utilized in the cited studies. Among the staphylococci isolated from the aerosol samples collected from air, there were two different species: Staphylococcus warneri and Staphylococcus epidermidis .…”
Section: Resultsmentioning
confidence: 99%
“…Different results were obtained by Wolny-Koładka et al [1] at the University of Agricultural in Cracow, where three dominant species-i.e., S. xylosus (18%), S. sciuri (17%) and S. hominis (15%)-were distinguished. At the same time, Brągoszewska et al [13] identified four staphylococcal species in three educational buildings in the industrial region of Upper Silesia, Poland, namely S. lentus, S. epidermidis, S. sciuri and S. chromogenes, while Brągoszewska et al [58] confirmed the dominance of S. lentus, S. epidermidis and S. chromogens in the high school gym located in an urban area of Southern Poland.…”
Section: Concentrations Of Mannitol-positive Staphylococci and Their Identificationmentioning
confidence: 96%
“…There is an extensive scientific literature about PM chemical composition, including bioaerosol, in crowded indoor environments, such as residential houses, hospitals, working sites, and aircraft ( [15][16][17][18], among others). However, only a few studies were specifically focused on the air quality of schools or academic environments [19][20][21][22][23][24][25][26][27][28], and only a few of these considered the bioaerosol and quantified its concentration. These studies were generally limited to some bio-components, such as viable fungi or bacteria, representing a fraction of only about 1% of total bioaerosol mass [29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%